Awareness of “Predatory” Open-Access Journals among Prospective Veterinary and Medical Authors Attending Scientific Writing Workshops - Christopher, Mary M.; Young, Karen M. (Frontiers in Veterinary Science, 2015)
Authors face many choices when selecting a journal for publication. Prospective authors, especially trainees, may be unaware of “predatory” online journals or how to differentiate them from legitimate journals. In this study we assessed awareness of open-access and predatory journals among prospective authors attending scientific writing workshops; our long-term goal was to inform educational goals for the workshops. We surveyed participants of writing workshops at veterinary and medical schools and an international conference over a 1-year period. The survey included 14 statements for respondents to indicate agreement level on a Likert-like scale and four questions on awareness of resources about predatory journals; respondents also defined “predatory journal”. A total of 145 participants completed the survey: 106 (73.1%) from veterinary schools and 86 (59.3%) graduate students or residents. Fewer faculty (vs trainees) agreed that open access was an important factor in deciding where to publish; faculty and postdoctoral researchers were more likely to expect to pay more to publish in an open-access journal. Most respondents (120/145, 82.7%) agreed/strongly agreed that the decision to accept a manuscript should not be influenced by publication charges, but 50% (56/112) indicated they “didn’t know” how publishing costs were supported. Of the 142 respondents who answered, 33 (23.0%) indicated awareness of the term “predatory journal”; 34 (23.9%) were aware of the Directory of Open Access Journals; 24 (16.9%) were aware of the Science “sting” article about predatory journals; and 7 (4.8%) were aware of Beall’s list. Most (93/144, 64.5%) definitions of predatory journals described poor but not predatory journal practices, and some respondents misunderstood the term completely. Mentors should help novice authors to be aware of predatory journals and to distinguish between legitimate and illegitimate open-access journals, thus selecting the best journal for their work.